1990
DOI: 10.1111/j.1151-2916.1990.tb07632.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Various Poly(vinyl butyral) Polymers Adsorbed onto Alumina

Abstract: Organic polymeric materials, often used as ceramic processing aids to assist in the fabrication of green bodies, are thought to be of a temporary nature, being easily removed by thermolysis at temperatures between 250" and 600°C. The interaction of various poly(viny1 butyral) binders with fine, high-purity alumina powder was investigated using variabletemperature Fourier-transform infrared spectroscopy and thermal gravimetric analysis. It was found that there was interaction between the functionality of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 1 publication
1
16
0
2
Order By: Relevance
“…Water tightly bound [12] to the filler surface possesses acidic properties which leads both to the acceleration of hydrolysis of the macromolecules and to their acidolysis, especially at elevated temperatures. The recent work of Howard et al [6] sheds some light on the interaction of PVB on alumina surface. They found that low molecular weight PVB's burned cleanly and the hydroxyl and acetate functional groups affected the adsorption of PVB on alumina.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Water tightly bound [12] to the filler surface possesses acidic properties which leads both to the acceleration of hydrolysis of the macromolecules and to their acidolysis, especially at elevated temperatures. The recent work of Howard et al [6] sheds some light on the interaction of PVB on alumina surface. They found that low molecular weight PVB's burned cleanly and the hydroxyl and acetate functional groups affected the adsorption of PVB on alumina.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The residual carbon in excess of 50 to 100 ppm would decrease the density and also affect many substrate properties like flexural strength, breakdown voltage [1] and dielectric constant [2]. In order to optimize the binder removal processes, some attention has been paid to studies such as polymer degradation mechanism [3][4][5], interactions of ceramics and binders [6][7][8], and effect of processing variables [9]. However information on kinetics of thermal degradation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…37 The adsorption of a polymer on a powder surface depends on the respective acid/base characteristics 38 and involves a competition for adsorption sites with solvent 39 and added dispersants. Howard et al 40 studied various PVBs adsorbed onto alumina in which the hydroxyl and acetate functionality of PVB provide the interaction sites between polymer and the alumina surface. Jean et al 39 studied the adsorption of PVB onto basic calcium borosilicate glass and acidic borosilicate glass and, depending on solvent composition, the acidic polymer PVB was more strongly adsorbed on the basic substrate.…”
Section: Comparison Of α-And Beta-alumina Tape Casting Using Pvb and mentioning
confidence: 99%
“…Several research studies have addressed the effect of incomplete removal of polymer during burnout on the mechanical, electrical, and magnetic properties of the sintered products [79][80][81][82][83][84][85][86][87][88][89][90][91]. The carbon content after thermal debinding was reported to be dependent on the following parameters:…”
Section: Carbon Contaminationmentioning
confidence: 99%